MENJADI DESA WISATA YANG AKUNTABEL DENGAN PELATIHAN PEMBUKUAN SEDERHANA BAGI STAKEHOLDER GLAMOUR CAMPING TERASERING MENOREH - Indrawati, Lucia Rita; Retnosari, Retnosari; Taufik, Ikhwan (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2024)
Problems faced by partners: (1) The Glamor Camping Terasering Menoreh tourist bookkeeper still does not fully understand proper bookkeeping, (2) Bookkeeping or financial records are still not optimal, (3) The partner's desire to become a Tourist Village that is Accountable for funds which he has managed (4) Expectations from partners so that the Tourism Village can develop and have competitiveness. Based on the problems faced by partners, the service team carried out several activities as a solution to this. Training was provided to Glamor Clamping Terasering Menoreh stakeholders. The first activity is presenting material regarding Accounting for business. The second activity is direct practice of bookkeeping or recording cash inflows and outflows and preparing financial reports. The third activity is to assist Stakeholders in communicating financial information periodically to the relevant community. The fourth activity is monitoring bookkeeping which has been carried out after training provided by the service team. The service team's hope is that financial recording or bookkeeping activities at the Menoreh Terrace Glamor Camping Tourism can run sustainably so that each stakeholder can monitor each other and maintain its sustainability. To achieve this, the service team carries out regular monitoring and evaluation so that the records carried out can be more accountable